Simulation-Based Analysis of Pressure Distribution on Rotary Soil Loosener Blades - V. I. Myalenko (Сельскохозяйственные машины и технологии)
The paper highlights the necessity of developing new energy-efficient machinery designs to implement minimum tillage technologies effectively. The use of rotary loosening tools for surface soil treatment at seed sowing depth offers several advantages over traditional implements in terms of both energy efficiency and reduced soil impact intensity. (Research purpose) The study aims to determine the distribution patterns of soil pressure on the blades of a rotary soil loosener under simulated loading conditions. (Materials and methods) A simulation-based modeling approach was used to analyze the loading of rotary loosener blades during their interaction with soil. Normal pressure values were measured at different points on the friction surface of the blades as they moved through a circular soil channel. These values were inferred by assessing wear intensity at various blade surface points. To facilitate this; a soft; easily erodible material was applied to the friction surface; and its wear intensity was measured using a magnetic induction method. (Results and discussion) The trajectory of blade movement in soil is described by a trochoidal path equation; while the loosening process itself resembles a «digging» motion. This process consists of two phases: penetration and retraction during which part of the loosened soil is displaced to the field surface. An equation was derived to describe blade movement in the soil as a function of its rotation angle spanning from the start of penetration to the retraction phase. Additionally; a theoretical model was developed to characterize blade loading patterns during soil interaction. Simulated blade loading enabled the measurement of abrasive wear intensity at various points on the friction surface. These measurements facilitated the development of a regression equation that defines the external loading characteristics of the loosener blades. (Conclusions) Soil cutting during loosening with a rotary soil loosener occurs through three cutting edges: the lower blade edge and the two side edges of the blade. This mechanism defines the nature of soil movement along the working surface of the blade. When manufacturing loosening tools; it is essential to ensure high wear resistance of the lower and side edges of the blade through reinforcement techniques.